Strategies and processes for the recovery of Gaza’s cultural landscape - Ficarelli, Loredana; Neglia, Giulia Annalinda (Plurimondi, 2025)
Years of protracted conflict in Gaza have devastated a region whose urban landscape was shaped over centuries by successive civilisations. The destruction has compromised the physical built environment and cultural heritage, severely damaging them and undermining social cohesion and the territory’s deeply embedded symbolic values. This paper first outlines a culturally sensitive reconstruction strategy for Gaza, drawing comparisons with previous cases and approaches to urban recovery and investigating the cultural significance of the different layers of heritage. The second section presents a methodological framework of principles and challenges for rebuilding a cultural urban landscape that has been severely damaged or completely destroyed. Finally, the paper concludes with targeted suggestions for rebuilding cultural urban landscapes, proposing actions and roles aimed at rehabilitating and restoring cultural and residential assets in crisis contexts. This ensures that recovery efforts respect and preserve the area’s identity and characteristics.